Caribbean mergers and acquisitions : country studies of the financial sectors of Guyana, Jamaica and Trinidad and Tobago - Khan, Glenn A. (Caribbean Centre for Monetary Studies St. AugustineTT, 2001)
Looks at the historical background of merger activity in general and discusses financial sector mergers in particular. Reviews some empirical evidence on the benefits of mergers. Provides background information on the Caribbean financial landscape before introducing the country studies on Guyana, Jamaica and Trinidad and Tobago.\n